Nanometer-scale phase separation and formation of delta ZrH2 in Cu-Zr binary amorphous alloys - Fadonougbo, Julien O.; Suh, Jin-Yoo; Shim, Cheol-Hwee; Kim, Gyeung-Ho; Fleury, Eric; Cho, Young Whan (ELSEVIER SCIENCE SA, 2017)
Different Cu-Zr alloys were hydrogenated under 100 bars of hydrogen pressure at different temperatures. The hydrogenation induced transformation of the initially amorphous phase into a polycrystalline structure characterized by its nanoscale (<5 nm), mostly composed of metallic Cu and ZrH2. Calorimetry measurements after hydrogenation showed a low temperature exothermic transformation occurring in the alloys hydrogenated at temperatures below 473 K, followed by multiple endothermic peaks at higher temperature attributed to dehydrogenation of different hydride phases. Activation barrier energies of the phase transformation were derived from Kissinger's method, and further characterization involving transmission electron microscopy revealed the existence of delta ZrH2 with cubic structure contrasting with the typical epsilon ZrH2 with tetragonal structure. This study evidences the effect of hydrogen pressure, temperature, and the alloy chemistry on the nature of the hydride formation in Cu-Zr binary amorphous alloys during the hydrogenation procedure. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: NI-NB-ZR; HYDROGEN PERMEABILITY; THERMAL-STABILITY; METALLIC GLASSES; CRYSTALLIZATION; PERMEATION; MEMBRANES; BEHAVIOR